2014
DOI: 10.1017/s1352465814000150
|View full text |Cite
|
Sign up to set email alerts
|

Does Catastrophizing of Bodily Sensations Maintain Health-Related Anxiety? A 14-Day Daily Diary Study with Longitudinal Follow-Up

Abstract: The present study bridges an important gap between theory and evidence. Results support cognitive behavioral theories and extend cross-sectional research asserting catastrophizing of bodily sensations maintains health-related anxiety over time. A cyclical, self-perpetuating pattern was observed in the present study wherein catastrophizing of bodily sensations and health-related anxiety contribute to one another over time. Results also suggest targeting catastrophizing of bodily sensations may reduce health-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
2
12
1
Order By: Relevance
“…This finding stands in contrast to cross sectional data, but could indicate that these constructs are involved more in the maintenance of health anxiety rather than its cause (see Marcus et al, 2007, andNorris &Marcus, 2014, for a review). The findings here differ from previous longitudinal studies which found that catastrophic misinterpretation (Gautreau et al, 2014) and emotional instability i.e. neuroticism (Ferguson, 2004), prospectively predicted health anxiety, but it seems that future studies must now consider metacognition in testing relationships of this kind.…”
Section: Accepted Manuscriptcontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding stands in contrast to cross sectional data, but could indicate that these constructs are involved more in the maintenance of health anxiety rather than its cause (see Marcus et al, 2007, andNorris &Marcus, 2014, for a review). The findings here differ from previous longitudinal studies which found that catastrophic misinterpretation (Gautreau et al, 2014) and emotional instability i.e. neuroticism (Ferguson, 2004), prospectively predicted health anxiety, but it seems that future studies must now consider metacognition in testing relationships of this kind.…”
Section: Accepted Manuscriptcontrasting
confidence: 99%
“…In the only study of its kind, catastrophizing of bodily sensations was shown to maintain health anxiety over a one month time period (Gautreau et al, 2014). Although this is a novel finding it is limited by the brevity of the time period between measurement occasions.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 82%
“…A more recent study also documented a similar trend. Specifically, Gautreau et al (2015) asked participants to record daily diary entries across 14 days and attend a follow-up session 14 days after the daily diary portion of the study concluded [ 12 ]. Results indicated that despite 97.6% of the participants attending the final laboratory session, participants only completed 75.2% to 84.1% of the daily diary entries across the daily diary portion of the study.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the results of Görgen and colleagues suggest that rumination directly contributes to health anxiety and that this effect is not mediated by depressive symptoms (Görgen et al, 2014). In addition, a recent study revealed the maintaining effects of rumination on health anxiety in college students (Gautreau et al, 2015). However, studies investigating rumination in patients with hypochondriasis are missing.…”
mentioning
confidence: 99%